A chromosomal genomics approach to assess and validate the desi and kabuli draft chickpea genome assemblies. Issue 6 (5th April 2014) - Ruperao, Pradeep; Chan, Chon‐Kit Kenneth; Azam, Sarwar; Karafiátová, Miroslava; Hayashi, Satomi; Čížková, Jana; Saxena, Rachit K.; Šimková, Hana; Song, Chi; Vrána, Jan; Chitikineni, Annapurna; Visendi, Paul; et al.
Summary With the expansion of next‐generation sequencing technology and advanced bioinformatics, there has been a rapid growth of genome sequencing projects. However, while this technology enables the rapid and cost‐effective assembly of draft genomes, the quality of these assemblies usually falls short of gold standard genome assemblies produced using the more traditional BAC by BAC and Sanger sequencing approaches. Assembly validation is often performed by the physical anchoring of genetically mapped markers, but this is prone to errors and the resolution is usually low, especially towards centromeric regions where recombination is limited. New approaches are required to validate reference genome assemblies. The ability to isolate individual chromosomes combined with next‐generation sequencing permits the validation of genome assemblies at the chromosome level. We demonstrate this approach by the assessment of the recently published chickpea kabuli and desi genomes. While previous genetic analysis suggests that these genomes should be very similar, a comparison of their chromosome sizes and published assemblies highlights significant differences. Our chromosomal genomics analysis highlights short defined regions that appear to have been misassembled in the kabuli genome and identifies large‐scale misassembly in the draft desi genome. The integration of chromosomal genomics tools within genome sequencing projects has the potential to significantly improve the construction and validation of genome assemblies. The approach could be applied both for new genome assemblies as well as published assemblies, and complements currently applied genome assembly strategies.